FINANCIAL MANAGEMENT AND BOOKKEEPING OF MSMES LEATHER CRAFTSMEN SUKARENGGANG - Indupurnahayu, Indupurnahayu; Sparta, Sparta; Prastowo, Bramastyo Bontas; Lysandra, Shanty (LPPM Univ. Ibn Khaldun Bogor, 2025)
This Community Service Program (PKM) aims to enhance leather artisans' understanding of the importance of bookkeeping in business at the Sukaregang Leather Centre, Garut City. The problems faced by MSME leather artisans include a lack of knowledge and skills in financial management, bookkeeping, and the preparation of basic financial statements. The solution offered is to provide training on financial management and bookkeeping. The results of this program show a significant improvement in knowledge regarding financial record-keeping, bookkeeping, and the preparation of basic financial statements. Thus, this Community Service Program (PKM) has had a positive impact on enhancing the potential of Garut’s MSME leather artisans for the future.